Prevalence of Escherichia Coli and Its Antimicrobial Susceptibility Profiles among Patients with UTI at Mulago Hospital, Kampala, Uganda. (1st February 2020) - Odongo, Isaac; Ssemambo, Ronald; Kungu, Joseph M.
Abstract : Background . Urinary tract infections (UTIs) remain the most common infections diagnosed in in- and outpatients as well as hospitalized patients. Current knowledge on antimicrobial susceptibility pattern for uropathogens is essential to effectively manage UTIs. This study aimed at determining the prevalence of E. coli and its antimicrobial susceptibility profiles among patients presenting with signs and symptoms of UTI in Mulago Hospital in Uganda. Methods . Midstream urine samples were collected from 100 patients presenting with signs and symptoms of UTI at the outpatient department of Mulago Hospital. The samples were cultured, and isolates of E. coli (predominant bacteria) are subjected to sensitivity testing against most commonly used antibiotics. Results . Out of 100 patients studied, E. coli was the most dominant with a prevalence of 10%. The prevalence was high among females (11.5%) compared with males (8.3%) and among the age group of ≤17 years. Escherichia coli isolates were highly susceptible to cefotaxime/clavulanic acid (100%) and nitrofurantoin (70%) but showed high resistance to cefuroxime (100%), ceftazidime (100%), nalidixic acid (90%), and ciprofloxacin (90%). Conclusion . Escherichia coli, the predominant uropathogen, showed significant multidrug resistance to antibiotics commonly prescribed for the management of UTIs. These findings should form a basis for preliminary decision making on the appropriate line of treatment for UTIs.